2016
DOI: 10.1088/1475-7516/2016/11/019
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly rotating neutron stars with a massive scalar field—structure and universal relations

Abstract: We construct rapidly rotating neutron star models in scalar-tensor theories with a massive scalar field. The fact that the scalar field has nonzero mass leads to very interesting results since the allowed range of values of the coupling parameters is significantly broadened. These deviations from pure general relativity can be very large for values of the parameters that are in agreement with the observations. The rapid rotation can magnify the differences several times compared to the static case. The univers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 77 publications
(117 reference statements)
1
62
0
1
Order By: Relevance
“…Pretorius [334] found that neutron stars (and not white dwarves) can scalarize and evade these observational bounds at the same time when −10 −3 ≲ β ≲ −3 and 10 −16 eV ≪ m s ≲ 10 −9 eV. Doneva and Yazadjiev [332] found that the universality in the I-Q relation is worse than that in GR, though the former remains equation-of-state universal within a few percent for a fixed f s M (where we recall f s is the stellar spin frequency). They also found that such a relation deviates from that in GR by 20% at most for β = −6 and Φ ∞ E,0 = 0.…”
Section: Scalar-tensor Theoriesmentioning
confidence: 95%
See 1 more Smart Citation
“…Pretorius [334] found that neutron stars (and not white dwarves) can scalarize and evade these observational bounds at the same time when −10 −3 ≲ β ≲ −3 and 10 −16 eV ≪ m s ≲ 10 −9 eV. Doneva and Yazadjiev [332] found that the universality in the I-Q relation is worse than that in GR, though the former remains equation-of-state universal within a few percent for a fixed f s M (where we recall f s is the stellar spin frequency). They also found that such a relation deviates from that in GR by 20% at most for β = −6 and Φ ∞ E,0 = 0.…”
Section: Scalar-tensor Theoriesmentioning
confidence: 95%
“…with m s is the mass of the scalar field. Spontaneous scalarization in such a theory was first studied in [333,334] for non-rotating neutron stars, and was later extended to slowly-rotating [335] and rapidly-rotating [332] neutron stars. The advantage of considering a massive theory is that if the scalar field mass is sufficiently large, non-GR modifications are screened and one is likely to evade Solar System and binary pulsar bounds on β for the massless theory.…”
Section: Scalar-tensor Theoriesmentioning
confidence: 99%
“…The structure and properties of slowly rotating neutron stars have also been explored under the influence of a massive scalar field. Doneva and Yazadjiev [27] investigated the dynamics of rapidly rotating neutron stars in the presence of a massive scalar field and concluded that deviations from GR can be large due to larger moment of inertia. Staykov et al [28] extended this work by considering a self-interacting potential along with a massive scalar field to analyze the behavior of static and slowly rotating neutron stars.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum mass that a differentially rotating neutron star can sustain therefore is higher for scalarized model than for GR models (with a strong dependence on the particular value of β). Notice that in the present paper we compare differentially rotating sequences of scaralized models with constant J to their GR counterparts, whereas in [24,25] sequences at the mass-shedding limit were considered (this explains the somewhat smaller deviations from GR, for same β, in the current results, with respect to those observerd in [24,25]).…”
Section: A Constant Angular Momentum Sequencesmentioning
confidence: 70%